Choroid plexus enlargement in patients with end-stage renal disease: implications for glymphatic system dysfunction - Park, Sihyung; Park, Bong Soo; Lee, Ho-Joon; Heo, Chang Min; Ko, Junghae; Lee, Dong Ah; Park, Kang Min (Frontiers in Neurology, 2024)
Objectives The choroid plexus plays a role in eliminating detrimental metabolites from the brain as an integral component of the glymphatic system. This study aimed to investigate alterations in choroid plexus volume in patients with end-stage renal disease (ESRD) compared with healthy controls. Methods We enrolled 40 patients with ESRD and 42 healthy controls. They underwent brain magnetic resonance imaging (MRI), specifically using three dimensional T1-weighted imaging. We analyzed choroid plexus volumes and compared them between patients with ESRD and healthy controls. The diffusion tensor image analysis along the perivascular space (DTI-ALPS) index was calculated. We compared the DTI-ALPS index between the ESRD patients and healthy controls. Additionally, we evaluated the association between choroid plexus volume and neuropsychological tests results in patients with ESRD. Results There were significant differences in choroid plexus volumes between patients with ESRD and healthy controls. The choroid plexus volumes in patients with ESRD were higher than those in healthy controls (1.392 vs. 1.138%, p < 0.001). The DTI-ALPS index in patients with ESRD was lower than that in healthy controls (1.470 ± 0.239 vs. 1.641 ± 0.266, p = 0.005). There were no differences in choroid plexus volumes between patients with ESRD, regardless of the presence of cognitive impairment. However, among the neuropsychological tests, the scores for word-list recognition in verbal memory were negatively correlated with the choroid plexus volume (r = −0.428, p = 0.006). Conclusion We demonstrated a significant enlargement of the choroid plexus volume in patients with ESRD compared to healthy controls. This finding suggests that patients with ESRD have glymphatic system dysfunction, which may be related to cognitive impairment.